Supporting the process of NFCS development in Zambia - Faniriantsoa, Rija; Nsengiyumva, Gloriose; Dinku, Tufa (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
IRI's partnership with AICCRA involves mainly building the capacity of National Meteorological Services (NMS) to develop and properly deliver useful and comprehensible climate data and information products for climate-informed decision-making. In Zambia, IRI has carried out a number of capacity building activities for the Zambia Meteorological Department (ZMD). These include (i) Advanced Climate Data Tool (CDT) introduced to some ZMD staff; (ii) IRI’s new Automatic Weather Station (AWS) Data Tool (ADT) for automatic weather station data organization and processing was installed and configured at ZMD, enabling ZMD to consolidate data from different networks ate one place; and (iii) the staff were also introduced to the IRI’s new Automatic Weather Station Data Tool (ADT) for automatic weather station data organization and processing.